Structural Rearrangements of Carbonic Anhydrase Entrapped in Sol-Gel Magnetite Determined by ATR–FTIR Spectroscopy - Ivanovski, Vladimir; Shapovalova, Olga E.; Drozdov, Andrey S. (MDPI AG, 2022)
Enzymatically active nanocomposites are a perspective class of bioactive materials that finds their application in numerous fields of science and technology ranging from biosensors and therapeutic agents to industrial catalysts. Key properties of such systems are their stability and activity under various conditions, the problems that are addressed in any research devoted to this class of materials. Understanding the principles that govern these properties is critical to the development of the field, especially when it comes to a new class of bioactive systems. Recently, a new class of enzymatically doped magnetite-based sol-gel systems emerged and paved the way for a variety of potent bioactive magnetic materials with improved thermal stability. Such systems already showed themself as perspective industrial and therapeutic agents, but are still under intense investigation and many aspects are still unclear. Here we made a first attempt to describe the interaction of biomolecules with magnetite-based sol-gel materials and to investigate facets of protein structure rearrangements occurring within the pores of magnetite sol-gel matrix using ATR Fourier-transform infrared spectroscopy.
Keywords: magnetite; sol-gel; carbonic anhydrase; protein secondary structure; entrapment; infrared spectroscopy